The Role of Islamic Economic Politics in Implementing Globalization ASEAN Economic Community (AEC) - Santika, Ana; Akbar, Estelee Elora; Rahmawan, Lutfi Hery (Majapahit Journal of Islamic Finance and Management, 2024)
Islamic economic opportunities in the MEA era, especially in Indonesia. As understood, the MEA is a cooperation and development of ASEAN integration that aims to play an important role in supporting economic integration, building a unique economic identity, and increasing inclusiveness in the Asian region. This study concludes that Indonesia can have the opportunity for sustainable Islamic economic development because, in terms of social justice in Islamic economics, it can encourage a more equitable distribution of income and reduce economic inequality. Second, Indonesian Islamic banking can be a national strength towards a golden Indonesia and help encourage economic inclusiveness among MEA member countries, by providing greater opportunities for all levels of society in Indonesia.